The Role of an Individual's Perception of their Partner's Oral Health in Heterosexual Couples - Manoelito Ferreira Silva Junior; Claudia Lobelli Chandler; Márcia Helena Baldani; Marília Jesus Batista; Maria da Luz Rosario de Sousa (Association of Support to Oral Health Research (APESB), 2021)
Objective: To analyze the role of an individual's perception of their partner's oral health in heterosexual couples. Material and Methods: The exploratory study with a qualitative and quantitative approach and data were collected in households in 2015. The quantitative data were analyzed using simple and multivariate binary logistic regression (p<0.05), and the qualitative using Thematic Content Analysis. Results: Of 143 participants, 113 (79.0%) were in a relationship and made up the final sample of the present study. Both women and men reported a small percentage of discomfort in relation to their partners' oral health (23.1% vs. 14.8%; p=0.199), and only a few had received complaints about their own oral health (20.7% vs. 10.7%; p=0.179). However, almost half of the sample had been told by their partner to see the dentist (47.6% vs. 31.0%; p=0.156), and of these, most were men (48.3% vs. 25.0%; p=0.022). The men that were more likely to be told by their partners to see the dentist (OR=5.82; 95% CI: 1.71-19.80) were upper-class (OR=3.35; 95% CI: 1.05-10.67), workers (OR=7.45; 95% CI: 1.62-34.20) who were dissatisfied with their oral health (OR=3.45; 95% CI: 1.13-10.51). The participants' reasons for complaining of their partners' oral health or for telling them to see the dentist were related to physiopathological clinical aspects and healthcare habits. Conclusion: The women told their male partners to seek dental services more often, and future studies should explore whether women are predictors of care and the validity of this information as an indicator of the oral health condition of their male partners.